Antidepressant-Like Activity of Methanolic Extract From Old Areca Nut Using Forced Swim Test Method In Mice (Mus Musculus) Tested Independently - Riryn Novianty; Nery Sofyanti; Fitra Audhi Ya’la (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2024)
This study aims to investigate the potential of methanolic extract from aged areca nut as an antidepressant using acute and sub-chronic Forced Swim Test (FST) methods. In the acute FST, mice were injected with methanolic extract doses of 10, 50, and 100 mg/kg intraperitoneally as a single dose to determine the dose with the best activity. Meanwhile, in the sub-chronic FST, the best dose was administered for 7 consecutive days, and a re-test was conducted on the seventh day after acute FST. A significant reduction in immobility time after acute treatment was only observed with a dose of 100 mg/kg. Therefore, mice were injected with this dose for the next 7 days. However, this dose did not significantly decrease immobility time based on the results of sub-chronic FST. Thus, the methanolic extract at a dose of 100 mg/kg was considered not potentially effective for continuous use. Phenolic compounds, steroids, and saponins as the main constituents in the extract did not induce toxic effects after treatment for 7 days.